Multiple Brucella melitensis lineages are driving the human brucellosis epidemic in Shaanxi Province, China: evidence from whole genome sequencing-based analysis - An, Cuihong; Nie, Shoumin; Luo, Boyan; Zhou, Dijia; Wang, Wenjing; Sun, Yangxin; Fan, Suoping; Liu, Dongli; Li, Zhenjun; Liu, Zhiguo; Chang, Wenhui (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionHuman brucellosis is a severe public concern in Shaanxi Province, China, and investigating the epidemiological relationship and transmission pattern of B. melitensis is necessary to devise control strategies.MethodsIn this study, a conventional bio-typing approach and whole genome sequencing of single-nucleotide polymorphisms (SNPs) were employed to identify 189 strains.ResultsBased on the conventional bio-typing, 189 Brucella strains were identified as B. melitensis, of which 14 were in bv. 1, 145 were in bv. 3, and 30 were variant, and the Brucella strains were distributed in all ten cities in Shaanxi Province. SNP analysis was used to identify genetic variation in 189 B. melitensis genomes, and maximum-likelihood was used to generate a phylogeny that identified two clades (A and B) and 19 sequence types (STs). The two clades were highly diverse and exclusively of Eastern Mediterranean origin. Clade B contained 18 STs (2-19), with most isolates originating from a broad swath, implying that multiple B. melitensis lineages circulated in Shaanxi. The 19 STs were composed of 3 to 46 strains isolated from different counties and years, suggesting that multiple cross-county brucellosis outbreak events are driven by multiple B. melitensis lineages. Global phylogenetic analysis revealed that clade A was close to GTIIb, and clade B was placed in the GTIIh lineage, expanding the known diversity of B. melitensis from China.ConclusionThe human brucellosis epidemic in Shaanxi is driven by multiple indigenous circulating B. melitensis lineages, the knowledge of which will contribute to devising a control strategy and providing the foundation for a comprehensive regional phylogeny of this important zoonotic pathogen.